Concentration-dependent improvement of gelling ability of soy proteins by preheating or ultrasound treatment. (December 2020) - Wang, Jiamei; Na, Xiaokang; Navicha, Willard Burton; Wen, Chengrong; Ma, Wuchao; Xu, Xianbing; Wu, Chao; Du, Ming
Abstract: In this study, effects of preheating or ultrasound treatment of soy proteins at different concentrations on the subsequent heat-induced aggregation and gelation behavior of these samples were investigated. Results showed that soy proteins with improved gelling ability were successfully obtained by preheating (100 °C, 30 min) samples at a protein concentration as high as 6% (w/v). The result was confirmed by increased storage modulus and viscosities of suspensions of the preheated soy proteins after reheating (100 °C, 30 min) at concentration of 10% (w/v). However, soy proteins with anti-aggregation and weakened gelation behaviors, as revealed by less increase in particle size and higher flow behavior indexes of tested suspensions at a concentration of 10% (w/v) after reheating, were obtained by preheating at lower concentrations (1%, 2%, and 4%, w/v). By comparison, all the samples pretreated by ultrasound at different protein concentrations showed greater gelling ability after reheating than the control sample. Results further revealed that soy proteins modified by preheating at lower protein concentrations showed greater loss of β-sheets structure and higher degree of unfolding. Whereas proteins pretreated by ultrasound showed lesser loss of β-sheets than the control sample. Findings of the study might provide useful insights on how the concentration of soy proteins during preheating or ultrasound treatment can be carefully controlled in order to obtain soy proteins with improved gelling ability. Highlights: Distinct gelling abilities of soy proteins were obtained by ultrasonic or preheating. Preheating at 6% (w/v) concentration resulted in improved gelling ability of soy proteins. Preheated at lower concentrations generated soy proteins with enhanced heat stability. Soy proteins with better gelling ability were obtained by ultrasonic than preheating.